Anders Breivik e la diagnosi di schizofrenia paranoide - Fargnoli, Domenico; Trevisan, Niccolò; Fargnoli, Francesco; Belli, Simone (Il sogno della farfalla, 2013)
After having analyzed the medical reports produced during the trial for the mass shootings at Oslo and Utoya in July 2011, this article criticizes the opinion of the experts which concluded that Anders B. Breivik was a terrorist affected by narcissistic personality disorder. This diagnosis, based on the DSM V-TR is the result of an uncritical forensic assessment which does not allow us to understand the murders. By interpreting events and symptoms in a different way ,and adopting elements of classical psychopathology such as «double bookkeeping» by E. Bleuler and «autistic activity» by E. Minkowski, it is possible to see symptoms of schizophrenia in the facts of Utoya. The article ends by proposing guidelines for the diagnosis of paranoid schizophrenia on the basis of the birth theory by Massimo Fagioli which the authors make reference to.